“Candidatus Galacturonibacter soehngenii” Shows Acetogenic Catabolism of Galacturonic Acid but Lacks a Canonical Carbon Monoxide Dehydrogenase/Acetyl-CoA Synthase Complex - Valk, Laura C.; Diender, Martijn; Stouten, Gerben R.; Petersen, Jette F.; Nielsen, Per H.; Dueholm, Morten S.; Pronk, Jack T.; van Loosdrecht, Mark C. M. (Frontiers in Microbiology, 2020)
Acetogens have the ability to fixate carbon during fermentation by employing the Wood-Ljungdahl pathway, which is highly conserved across Bacteria and Archaea. In a previous study, product stoichometries in galacturonate-limited, anaerobic enrichment cultures of “Candidatus Galacturonibacter soehngenii”, from a novel genus within the Lachnospiraceae, suggested the simultaneous operation of a modified Entner-Doudoroff pathway for galacturonate fermentation and a Wood-Ljungdahl pathway (WLP) for acetogenesis. However, a draft metagenome-assembled genome (MAG) based on short reads did not reveal homologs of genes encoding a canonical WLP carbon-monoxide-dehydrogenase/acetyl-Coenzyme A synthase (CODH/ACS) complex. In this study, NaH13CO3 fed to chemostat-grown, galacturonate-limited enrichment cultures of “Ca. G. soehngenii” was shown to be incorporated into acetate. Preferential labelling of the carboxyl group of acetate was consistent with hetero-acetogenesis via a WLP in which the methyl group of acetate was predominately derived from formate. This interpretation was further supported by high transcript levels of a putative pyruvate-formate lyase gene and very low transcript levels of a candidate gene for formate dehydrogenase. Reassembly of the “Ca. G. soehngenii” MAG with support from long-read nanopore sequencing data produced a complete MAG, which confirmed the absence of canonical CODH/ACS-complex genes homologs. However, high CO-dehydrogenase activities were measured in cell extracts of “Ca. G. soehngenii” enrichment cultures, contradicting the absence of corresponding homologues in the MAG. Based on the highly conserved amino-acid motif associated with anaerobic Ni-CO dehydrogenase proteins, a novel candidate was identified which could be responsible for the observed activities. These results demonstrate operation of a hetero-acetogenic pathway, most probably as an yet unresolved variant of the Wood-Ljungdahl pathway, in anaerobic, galacturonate-limited cultures of “Ca. G. soehngenii”.